Construction of N-doped TiO2/MoS2 heterojunction with synergistic effect for enhanced visible photodegradation activity. (September 2018) - Tang, Xinde; Wang, Zhengrong; Huang, Wei; Jing, Quanwei; Liu, Ning
Graphical abstract: An N-doped TiO2 /MoS2 heterojunction constructed by two-dimension MoS2 nanosheets and N-doped TiO2 nanoparticles was successfully synthesized by a hydrothermal method, which achieved more enhanced visible-light photocatalytic activity due to the formation of heterostructure between MoS2 and N-doped TiO2, which possesses the synergistic effect of enhanced adsorption of MB on catalyst surface, improved visible light absorption and efficient charge transport and separation. Highlights: An N-doped TiO2 /MoS2 heterojunction is successfully synthesized by a hydrothermal method. N-doped TiO2 /MoS2 heterojunction photocatalyst exhibits enhanced visible photodegradation activity. The synergistic effect is between N-doping and coupling with MoS2 . Superoxide radicals (O2 − ) and photogenerated holes (h + ) are chiefly responsible for the degradation process. Abstract: An N-doped TiO2 /MoS2 heterojunction photocatalyst constructed by two-dimension MoS2 nanosheets and N-doped TiO2 nanoparticles was successfully synthesized by a hydrothermal method. The synthesized N-TiO2 /MoS2 composites were characterized by XRD, XPS, TEM, UV–vis DRS and PL, and its visible photocatalytic activity was evaluated by degradation of methylene blue. The results showed that N-doped TiO2 /MoS2 heterojunction photocatalyst achieved more enhanced photocatalytic activity compared with pure TiO2, MoS2 and N-doped TiO2 for degradation of MB. Trapping tests with different scavengers indicated that not hydroxyl radicals (OH) but superoxide radicals (O2 − ) and photogenerated holes (h + ) were highly responsible for the degradation process. The reusable experiments showed that the prepared N-doped TiO2 /MoS2 heterojunction photocatalyst was stable during the photodegradation of MB and will have practical applications for environmental remediation.